Double inferior vena cava systems during retroperitoneal surgery: Description of a systematic approach to a rare and challenging anatomic variant - German J. Chaud, MD; Louis Lacombe, MD; François Dagenais, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Detailed knowledge of the various venous anomalies is important to optimize the surgical approach and minimize catastrophic complications during retroperitoneal surgery. We report a rare case of an isolated left inferior vein cava (IVC) in a patient with left renal cell carcinoma with level IV IVC thrombus extension, which was successfully treated with terminal–lateral anastomoses between the left and right IVC. We also reviewed the types of duplicated IVCs and discussed the intraoperative management.